Pengaruh budaya organisasi, komunikasi dan kompensasi terhadap kinerja pegawai di kantor sekretariat DPRD Kabupaten Pinrang - Rizaly, Muhammad; Rina; Hafipah (STIM-LPI Makassar, 2025)
This study aims to determine and analyze the influence of organizational culture, communication, and compensation on employee performance at the Secretariat Office of the Pinrang Regency DPRD. Data collection techniques include observation, questionnaires, interviews, and documentation. This research was carried out at the Pinrang Regency DPRD Secretariat Office, lasting approximately 2 (two) months, from May to June 2024. The research population is all Pinrang Regency DPRD Secretariat Office employees, totaling 90. Using a saturated sampling technique, the sample is the entire population, namely 90 employees. The study results have been tested for validity and reliability, as well as classical assumptions in the form of normality assumptions, Multicollinearity assumptions, and heteroskedasticity assumption tests. The data analysis method uses multiple linear analysis techniques and hypothesis tests. The results of the analysis show that (1) organizational culture has a positive and significant effect on employee performance at the Pinrang Regency DPRD Secretariat Office, (2) communication has a positive and significant effect on employee performance at the Pinrang Regency DPRD Secretariat Office (3) compensation has a positive and significant effect on employee performance the Secretariat Office of the Pinrang Regency DPRD, (4) the culture of organization, communication, and compensation simultaneously has a positive and significant effect on the performance of employees at the Secretariat Office of the Pinrang Regency DPRD.